PENERIMAAN GENERASI Z SURABAYA PADA KARAKTERISTIK GENERASI Z DALAM IKLAN GOJEK “SOLUSI MASALAH OVERTHINKING PILIH MAKANAN, ADA DI VIDEO INI!” - Mukhammad Shobri Kamil; Ahmad Zamzamy; Didiek Tranggono; Dyva Claretta (Linimasa : Jurnal Ilmu Komunikasi, 2023)
This study focused to investigate how the Gen Z in Surabaya receives the representation of Gen Z characteristics that are visualized in the Gojek advertisement "SOLUSI MASALAH OVERTHINKING PILIH MAKANAN, ADA DI VIDEO INI!". The advertisement attempts to portray Gen Z's characteristics, such as overthinking, commitment issues in relationships, job-hopping, and the tendency to believe in or use horoscope predictions. Previous literature suggests that Gen Z tends to exhibit these characteristics, which motivated the researcher to investigate how the Surabaya Gen Z population responds to this advertisement's portrayal of their traits. This study uses a qualitative descriptive research method with Stuart Hall encoding-decoding theory to analyze the reception. The informants consist of 11 Gen Z individuals with various backgrounds from Surabaya city. The research data collection techniques include in-depth interviews, observations, and literature reviews. The study results indicate that the informants have different responses due to their varying backgrounds. Four informants, 1, 3, 8, and 10, included in the dominant-hegemonic position, while the other seven, 2, 4, 5, 6, 7, 9, and 11, are in the negotiation position. The researcher did not identify any informants in the opposition position. Keywords: Reception Analysis, Gen Z Characteristics, and Advertisement